Wild Pig Hunting in Petungkriono - Pujo Semedi (Humaniora, 2010)
Anthropologists have been studying hunting from the economic, ecological, and symbolical perspectives. The third perspective has been used to comprehend the hunting activities among the farmers of Petungkriono who have used hunting to show masculinity. Further investigation has revealed that the arena is created as a compensation for the fragile position of the local male inhabitants in the household social economic condition as connected to the matrilinear land inheritance system.